322. Evaluation of the BioFire® Bone and Joint Infection (BJI) Panel for the Detection of Microorganisms and Antimicrobial Resistance Genes in Synovial Fluid Specimens. (31st December 2020) - Graue, Corrin; Schmitt, Bryan H; Waggoner, Amy; Laurent, Frederic; Abad, Lelia; Bauer, Thomas; Mazariegos, Irving; Balada-Llasat, Joan-Miquel; Horn, Jarid; Wolk, Donna; Jefferis, Alexa; Hermans, Mirjam; et al.
Abstract: Background: Bone and Joint Infections (BJIs) present with non-specific symptoms that may include pain, swelling, and fever and are associated with high morbidity and significant risk of mortality. BJIs can be caused by a variety of bacteria and fungi, including anaerobes and microorganisms that can be challenging to culture or identify by traditional microbiological methods. Clinicians primarily rely on culture to identify the pathogen(s) responsible for infection. The BioFire ® Bone and Joint Infection (BJI) Panel (BioFire Diagnostics, Salt Lake City, UT) is designed to detect 15 gram-positive bacteria (including seven anaerobes), 14 gram-negative bacteria (including one anaerobe), two yeast, and eight antimicrobial resistance (AMR) genes from synovial fluid specimens in about an hour. The objective of this study was to evaluate the performance of an Investigational Use Only (IUO) version of the BioFire BJI Panel compared to various reference methods. Methods: Remnant synovial fluid specimens, which were collected for routine clinical care at 13 study sites in the US and Europe, underwent testing using an IUO version of the BioFire BJI Panel. Performance of this test was determined by comparison to Standard of Care (SoC) consisting of bacterial culture performed at each study site according to their routine procedures. Results: A total of 1544 synovial fluid specimens were collected and tested with the BioFire BJI Panel. The majority of specimens were from knee joints (77.9%) and arthrocentesis (79.4%) was the most common collection method. Compared to SoC culture, overall sensitivity was 90.2% and specificity was 99.8%. The BioFire BJI Panel yielded a total of 268 Detected results, whereas SoC yielded a total of 215 positive results for on-panel analytes. Conclusion: The BioFire BJI Panel is a sensitive, specific, and robust test for rapid detection of a wide range of analytes in synovial fluid specimens. The number of microorganisms and resistance genes included in the BioFire BJI Panel, together with a reduced time-to-result and increased diagnostic yield compared to culture, is expected to aid in the timely diagnosis and appropriate management of BJIs. Disclosures: Benjamin von Bredow, PhD, BioFire (Grant/Research Support) Jennifer Dien Bard, PhD, BioFire Diagnostic (Consultant, Scientific Research Study Investigator) Bart Kensinger, PhD, BioFire Diagnostics (Employee) Benedicte Pons, PhD, bioMerieux SA (Employee) Corinne Jay, PhD, bioMerieux SA (Employee)